2019
DOI: 10.1096/fj.201901582r
|View full text |Cite
|
Sign up to set email alerts
|

l‐Fucose prevention of renal ischaemia/reperfusion injury in Mice

Abstract: In a recent study, we identified a fucosylated damage‐associated ligand exposed by ischemia on renal tubule epithelial cells, which after recognition by collectin‐11 (CL‐11 or collectin kidney 1 (CL‐K1)), initiates complement activation and acute kidney injury. We exploited the ability to increase the local tissue concentration of free l‐fucose following systemic administration, in order to block ligand binding by local CL‐11 and prevent complement activation. We achieved a thirty‐five‐fold increase in the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
(166 reference statements)
4
21
0
Order By: Relevance
“…The role of complement effectors in renal IRI has been extensively described [10,11]. In addition, more recent studies have identified a primary role for the lectin pathway of complement activation, in particular the contribution of the PRM known as collectin-11 (CL-11) and the potential for blocking its downstream effects [12,13]. Evidence points to a major fucosylated ligand recognized by CL-11 on hypoxic tissue [13] and has highlighted the feasibility to block CL-11 binding to this ligand by treatment with high concentrations of soluble L-fucose [12].…”
Section: Complement In Irimentioning
confidence: 99%
“…The role of complement effectors in renal IRI has been extensively described [10,11]. In addition, more recent studies have identified a primary role for the lectin pathway of complement activation, in particular the contribution of the PRM known as collectin-11 (CL-11) and the potential for blocking its downstream effects [12,13]. Evidence points to a major fucosylated ligand recognized by CL-11 on hypoxic tissue [13] and has highlighted the feasibility to block CL-11 binding to this ligand by treatment with high concentrations of soluble L-fucose [12].…”
Section: Complement In Irimentioning
confidence: 99%
“…The treatment was remarkable, since equilibration of free fucose within the renal space to a concentration 10 times the normal level partially protected the mice against loss of renal function induced by IRI. Mice lacking CL-11 gained no additional protection from L-fucose therapy, indicating that the therapeutic effect in this model was largely CL-11 dependent [48].…”
Section: The Role Of L-fucosementioning
confidence: 87%
“…The biochemical nature of the fucosylated ligand on damaged tissue and the precise timing of its interaction with CL-11 need to be more fully understood to allow potential clinical exploitation. However, in theory, a large enough increase in local L-fucose concentration within the kidney will block CL-11 binding and/or activation of complement, and in doing so will protect the donor kidney from the effects of IRI, and this has been shown in mice [48]. L-fucose monosaccharide is an excellent candidate for this because a number of studies have shown its safety at high levels in both mice and humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, as our research team discovered that fucose is testified to competent in different types of diseases, including colitis, renal ischemia/reperfusion injury and high-fat diet-induced obesity and hepatic steatosis ( 10 , 24 , 25 ), it has also been demonstrated to impact the microbial ecosystem ( 11 ). Notably, fucose may decrease pathogen virulence through certain bacterium's metabolic pathway, such as Salmonella enterica ( 12 ).…”
Section: Discussionmentioning
confidence: 99%